Response of midland sorghum varieties to different intra-row spacing at kaffa zone south western Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
The experiment was conducted to determine optimum plant spacing and suitable variety and as well as to identify the interaction effect of varieties and Intra-row spacing on the yield of sorghum. The experiment having a factorial arrangement of three varieties (Geremew, Lalo and farmer’s local variety) and three intra-row levels (10 cm, 15 cm and 20 cm) was laid out in randomized complete block design (RCBD) with three replications. According to the current results, varieties were significantly (p